1963
DOI: 10.1063/1.1734570
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an Electric Field on the Dielectric Loss of the Liquid Crystal p-Azoxyanisole

Abstract: This work involves the alignment of molecules in the anisotropic liquid phase of p-azoxyanisole due to externally applied dc and ac electric fields and walls of the sample holder. Microwave techniques involving dielectric measurements are used to provide a measure of the alignment. Results are discussed which suggest that for very pure samples an alignment should be produced with the long axes of the molecules perpendicular to the externally applied electric field. The alignment with the long axes parallel to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1968
1968
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Since the director of the phase spontaneously aligns with the magnetic field, such experiments are somewhat tricky to perform. Several procedures have been developed to overcome this problem; e.g., slow rotation of the sample tube around an axis perpendicular to the magnetic field, , fast spinning of the sample tube around an axis at the angle θ LD to the magnetic field, or use of an electric field. Since in the present system the anisotropy of the diamagnetic susceptibility of the phase is only slight, the magnetic torque that tends to orient the director with the field is small. In addition, the rotational viscosity of the phase is so high that the reorientation of the director is a fairly slow process (lasting for minutes).…”
Section: Introductionmentioning
confidence: 99%
“…Since the director of the phase spontaneously aligns with the magnetic field, such experiments are somewhat tricky to perform. Several procedures have been developed to overcome this problem; e.g., slow rotation of the sample tube around an axis perpendicular to the magnetic field, , fast spinning of the sample tube around an axis at the angle θ LD to the magnetic field, or use of an electric field. Since in the present system the anisotropy of the diamagnetic susceptibility of the phase is only slight, the magnetic torque that tends to orient the director with the field is small. In addition, the rotational viscosity of the phase is so high that the reorientation of the director is a fairly slow process (lasting for minutes).…”
Section: Introductionmentioning
confidence: 99%
“…However, these instabilities have been broadly studied in the past century on molecular liquid crystals in a very different geometry, whereby the field is applied parallel in the direction of highest confinement, parallel to the viewing direction by using transparent electrodes, and the variety of patterns observed in this configuration already justified an effort of classification. (Blinov et al 1982;Blinov 1986Blinov , 1998 The physical interpretation of the underlying mechanisms for this instability is usually captured by the now standard Carr-Helfrich mechanism, (Carr 1963;Helfrich 1969) which was successfully described theoretically (Dubois-Violette et al 1971;Smith et al 1975) and confirmed by experiments. (Orsay Liquid Crystal Group 1970) It is usually divided in a conductive regime at lower frequencies and a dielectric regime at higher frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…The origin of this term lies in the early work of Carr in 1963 [37], in which conduction-induced alignment in nematic liquid crystal was studied extensively. It was suggested that the long molecular axes undergo a specific alignment parallel to the walls of the container due to the presence of impurities in the samples.…”
Section: Nonuniform Director Profilesmentioning
confidence: 99%